Plasmodium falciparum K13 Mutations Differentially Impact Ozonide Susceptibility and Parasite Fitness In Vitro - Judith Straimer; Nina F. Gnädig; Barbara H. Stokes; Michelle Ehrenberger; Audrey A. Crane; David A. Fidock (mBio, 2017)
ABSTRACT The emergence and spread in Southeast Asia of Plasmodium falciparum resistance to artemisinin (ART) derivatives, the cornerstone of first-line artemisinin-based combination therapies (ACTs), underscore the urgent need to identify suitable replacement drugs. Discovery and development efforts have identified a series of ozonides with attractive chemical and pharmacological properties that are being touted as suitable replacements. Partial resistance to ART, defined as delayed parasite clearance in malaria patients treated with an ART derivative or an ACT, has been associated with mutations in the P. falciparum K13 gene. In light of reports showing that ART derivatives and ozonides share similar modes of action, we have investigated whether parasites expressing mutant K13 are cross-resistant to the ozonides OZ439 (artefenomel) and OZ227 (arterolane). This work used a panel of culture-adapted clinical isolates from Cambodia that were genetically edited to express variant forms of K13. Phenotypic analyses employed ring-stage survival assays (ring-stage survival assay from 0 to 3 h [RSA0–3h]), whose results have earlier been shown to correlate with parasite clearance rates in patients. Our results document cross-resistance between OZ277 and dihydroartemisinin (DHA), a semisynthetic derivative of ART, in parasites carrying the K13 mutations C580Y, R539T, and I543T. For OZ439, we observed cross-resistance only for parasites that carried the rare K13 I543T mutation, with no evidence of cross-resistance afforded by the prevalent C580Y mutation. Mixed-culture competition experiments with isogenic lines carrying modified K13 revealed variable growth deficits depending on the K13 mutation and parasite strain and provide a rationale for the broad dissemination of the fitness-neutral K13 C580Y mutation throughout strains currently circulating in Southeast Asia. IMPORTANCE ACTs have helped halve the malaria disease burden in recent years; however, emerging resistance to ART derivatives threatens to reverse this substantial progress. Resistance is driven primarily by mutations in the P. falciparum K13 gene. These mutations pose a threat to ozonides, touted as promising alternatives to ARTs that share a similar mode of action. We report that DHA was considerably more potent than OZ439 and OZ277 against ART-sensitive asexual blood-stage parasites cultured in vitro. We also document that mutant K13 significantly compromised the activity of the registered drug OZ277. In contrast, OZ439 remained effective against most parasite lines expressing mutant K13, with the exception of I543T that merits further monitoring in field-based OZ439 efficacy studies. K13 mutations differed considerably in their impact on parasite growth rates, in a strain-dependent context, with the most prevalent C580Y mutation being fitness neutral in recently culture-adapted strains from Cambodia, the epicenter of emerging ART resistance.